Effect of race distance on performance fatigability in male trail and ultra‐trail runners. (12th July 2021) - Temesi, John; Besson, Thibault; Parent, Audrey; Singh, Benjamin; Martin, Vincent; Brownstein, Callum G.; Espeit, Loïc; Royer, Nicolas; Rimaud, Diana; Lapole, Thomas; Féasson, Léonard; Millet, Guillaume Y.
Abstract: The etiology of changes in lower‐limb neuromuscular function, especially to the central nervous system, may be affected by exercise duration. Direct evidence is lacking as few studies have directly compared different race distances. This study aimed to investigate the etiology of deficits in neuromuscular function following short versus long trail‐running races. Thirty‐two male trail runners completed one of five trail‐running races as LONG (>100 km) or SHORT (<60 km). Pre‐ and post‐race, maximal voluntary contraction (MVC) torque and evoked responses to electrical nerve stimulation during MVCs and at rest were used to assess voluntary activation and muscle contractile properties of knee‐extensor (KE) and plantar‐flexor (PF) muscles. Transcranial magnetic stimulation (TMS) was used to assess evoked responses and corticospinal excitability in maximal and submaximal KE contractions. Race distance correlated with KE MVC ( ρ = −0.556) and twitch ( ρ = −0.521) torque decreases ( p ≤ .003). KE twitch torque decreased more in LONG (−28 ± 14%) than SHORT (−14 ± 10%, p = .005); however, KE MVC time × distance interaction was not significant ( p = .073). No differences between LONG and SHORT for PF MVC or twitch torque were observed. Maximal voluntary activation decreased similarly in LONG and SHORT in both muscle groups ( p ≥ .637). TMS‐elicited silent period decreased in LONG ( p = .021) but not SHORT ( p = .912). Greater muscle contractile property impairment in longer races, not central perturbations, contributed to the correlation between KE MVC loss and race distance. Conversely, PF fatigability was unaffected by race distance.